Chaenomeles japonica (Maleae, Amygdaloideae, Rosaceae): validation of six Alberts Tīcs’ cultivar names and two new synonyms for the species - Stalažs, Arturs; Sviķe, Silga; Veckalne, Aiga (Phytotaxa, 2022)
Chaenomeles is a rosaceous genus of Asian origin with eight species, including four artificially created hybrids. Several species of this genus are used in many countries for ornamental plants and fruit production. As a result of many years of breeding work in Latvia, Alberts Tīcs selected six Chaenomeles japonica (Japanese quince) cultivars. Unfortunately, when publishing the descriptions of his cultivars, he does not comply with the requirements of the International Code of Nomenclature for cultivated plants because the names of newly introduced cultivars are not validly published. In his publications on the cultivation of Chaenomeles, Tīcs has introduced new scientific names, which have been published without complying with the requirements of the International Code of Nomenclature for algae, fungi, and plants. The validation of Tīcs’ cultivar names has been performed here, and the names—Chaenomeles maulei f. pomifera-inermis  nom. nud. and Chaenomeles ×pomoidea  nom. nud.—have been recognized as new synonyms of Chaenomeles japonica. Descriptions have been provided for all Alberts Tīcs’ cultivars.